Change of Gut Microbiota and its Role in Tuberculosis - Mustika, Syifa; Michaela, Cleine (The Indonesian Society for Digestive Endoscopy, 2024)
Introduction: Tuberculosis (TB) is a prevalent infectious illness and a leading cause of death globally. An alteration in the microbial communities heightens vulnerability to tuberculosis. The changes mentioned below are responsible for pulmonary disease, as well as a decrease in the body's ability to resist the invasion of harmful external microorganisms or the depletion of beneficial bacteria. Literature review: Adults diagnosed with pulmonary tuberculosis exhibited a stool microbiome that contained a greater abundance of anaerobic microorganisms. This was found to be linked to proinflammatory immunological pathways in the host and was also associated with the severity of tuberculosis. Relapsed tuberculosis was correlated with elevated Actinobacteria and Proteobacteria levels and decreased Bacteroidetes levels. The pathogenesis of Mycobacterium TB infection and the onset of tuberculosis symptoms may be influenced by changes in the gut-lung microbiome axis. Medication availability, efficacy, and adverse effects can be impacted by the gut flora in several ways. Currently, researchers recommend exploring the potential of combining TB medicine with gut-focused probiotics to improve treatment response and outcomes. Conclusion: The microbiome has the potential to be a modifiable risk factor for tuberculosis. The human microbiota may have a role in the development of M. tuberculosis and treatment for tuberculosis can disrupt the balance of microorganisms, leading to dysbiosis, which can in turn impact the host's immune system. Probiotics and postbiotics demonstrate anti-tuberculosis properties, suggesting their ability to address problems arising from the use of various antibiotics.Keywords: Tuberculosis, microbiome, gut-lung axis